Comparing single-patient and multi-patient room intensive care units: a multicenter cohort study on architectural differences and clinical significance in South Korea - Jeong, Daun; Lee, Donghyoun; Yoon, Kyoung Won; Kim, Hyo Jin; Choi, Sun Young; Park, Chi-Min (Acute and critical care, 2025)
Background: The design of intensive care units (ICUs) is increasingly acknowledged as a crucial factor affecting patient outcomes. Transitioning from multi-bed patient rooms (MPRs) to single-bed patient rooms (SPRs) aims to improve infection control, patient privacy, and quality of care. However, concerns remain regarding potential patient isolation and reduced staff situational awareness. This study aims to evaluate clinical outcomes in SPR-structured ICUs compared to mixed SPR and MPR ICUs.Methods: This multicenter retrospective cohort study was conducted across three university-affiliated tertiary hospitals between April 2022 and August 2023. The study population included ICU patients aged ≥18 years, excluding those admitted to cardiac and neonatal ICUs. Outcomes assessed included ICU mortality and severity scores based on Simplified Acute Physiology Score 3 and Acute Physiology and Chronic Health Evaluation II scores. Results: This study included 3,179 ICU patients across three sites: Site A consisted exclusively of SPRs, while sites B and C had mixed SPR and MPR arrangements. ICU mortality rates were 8.3%, 15.2%, and 9.7% for sites A, B, and C, respectively (P<0.001). Propensity score matching and logistic regression analysis demonstrated that SPRs were associated with significantly reduced ICU mortality (adjusted odds ratio, 0.54; 95% CI, 0.40–0.73). Conclusion: SPRs were associated with a protective effect, reducing ICU mortality. Clinical outcomes in ICUs appear to be influenced by structural design improvements alongside other clinical factors.